'It's history in the making all around us': examining COVID-19 through the lenses of HIV and epidemic history. Issue 11 (1st November 2021) - Braksmajer, Amy; London, Andrew S.
Abstract: Research increasingly considers how collective narratives/experiences of HIV influence understandings of and responses to COVID-19 among men who have sex with men and how these discussions articulate with the larger literature on the social significance of epidemics. Drawing on interviews with 30 men who have sex with men, as well as discussion of epidemics as dramaturgical events, this study aimed to determine how men living in the USA make sense of COVID-19 in the light of their collective knowledge and/or memories of the HIV pandemic. Participants experienced progressive revelations regarding COVID-19's seriousness and constructed frameworks with which to manage the unpredictability of infection. Participants also believed that the initial public response to COVID-19 on the part of the US federal government, health officials and the scientific community, although inadequate, was stronger and more extensive than the response had been to HIV. As communities and the USA negotiated their pandemic responses, participants negotiated their own personal responses with incomplete, uncertain, dynamic and conflicting information. This study provides evidence regarding the social organisation of a contemporary pandemic and how individuals perceive and guard against risk, assign responsibility for virus transmission and acquisition, and navigate the threat of a potentially deadly infection.